New records and a confirmation of three perlodid species in China, with additional notes and images of Rauserodes epiproctalis (Zwick, 1997)(Plecoptera: Perlodidae) - Huo, Qing-Bo; Chen, Zhen-Ning; Kong, Xiang-Bo; Du, Yu-Zhou (Zootaxa, 2020)
Three species of the family Perlodidae are newly reported or confirmed for China, Isoperla asiatica Raušer from Arxan, Inner Mongolia Autonomous Region, Isoperla eximia Zapekina-Dulkeit from Changbai Mountain, Jilin Province, and Mesoperlina capnoptera (McLachlan, 1886) from Xinjiang Uygur Autonomous Region. Based on new material, additional taxonomic notes and images of another perlodid stonefly, Rauserodes epiproctalis (Zwick, 1997) is provided.